1993
DOI: 10.1172/jci116173
|View full text |Cite
|
Sign up to set email alerts
|

Transport defects of rabbit medullary thick ascending limb cells in obstructive nephropathy.

Abstract: To characterize the sodium transport defect responsible for salt wasting in obstructive nephropathy, the major sodium transporters in the medullary thick ascending limb (mTAL), the apical Na-K-2CI cotransporter and the basolateral Na-KATPase, were studied in fresh suspensions of mTAL cells and outer medulla plasma membranes prepared from obstructed and untreated kidneys. Oxygen consumption (Qo2) studies in intact cells revealed marked reductions in the inhibitory effects of both furosemide and ouabain on Qo2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…We consider such a mechanism, however, as less likely, because one would expect that the recirculating transepithelial salt transport rate in hydronephrotic kidneys should be lower than the tubular salt transport in intact, filtering kidneys. In fact, it has already been shown that ureteral occlusion leads to a rapid decline of salt transport by the TALH (18), which is compatible with the reduced expression of NKCC2 in our study. A reduction of tubular salt transport should increase basal COX-2 expression and at the same time attenuate the stimulation of COX-2 expression by maneuvers inhibiting tubular salt transport.…”
Section: Discussionsupporting
confidence: 92%
“…We consider such a mechanism, however, as less likely, because one would expect that the recirculating transepithelial salt transport rate in hydronephrotic kidneys should be lower than the tubular salt transport in intact, filtering kidneys. In fact, it has already been shown that ureteral occlusion leads to a rapid decline of salt transport by the TALH (18), which is compatible with the reduced expression of NKCC2 in our study. A reduction of tubular salt transport should increase basal COX-2 expression and at the same time attenuate the stimulation of COX-2 expression by maneuvers inhibiting tubular salt transport.…”
Section: Discussionsupporting
confidence: 92%
“…Loop diuretics combined with oral salt supplementation are also an effective chronic therapy for the syndrome of inappropriate antidiuretic hormone (106), blunting the countercurrent mechanism, increasing water excretion, and correcting the associated hyponatremia. An acquired dysfunction of NKCC2 after ureteral obstruction can in turn lead to the salt wasting and impaired urinary concentrating ability that is characteristic of postobstructive renal function (107).…”
Section: Pathophysiology Of the Talmentioning
confidence: 99%
“…5). On the other hand, the relative conductances of Cl-and K+ were, respectively, decreased and increased in the CCD from UUO animals (14) ( ) (9) (8) (+ CONTROL (16) (-) (9) *tt .…”
Section: Discussionmentioning
confidence: 94%
“…However, the mechanisms underlying these disorders have not been fully evaluated. Only a few studies have assessed them at a segmental level (10)(11)(12)(13)(14)(15). The in vitro microperfusion studies of the rabbit CCD have demonstrated that unilateral ureteral obstruction (UUO) led to decreases in the lumen-negative transepithelial voltage (10,11) as well as in Na'-K+-ATPase activity (12) and in Na'-K' pump in situ turnover (13) in the CCD from obstructed rat kidneys after UUO.…”
mentioning
confidence: 99%